Weight changes, sodium levels, and performance in the South African ironman triathlon - Sharwood, K.; Collins, M.; Goedecke, J.; Wilson, G.; Noakes, T. (Clinical Journal of Sport Medicine, 2002)
Objective: To establish relationships between body weight changes and serum sodium during and after an Ironman Triathlon, and postrace fluid status and rectal temperature, including the incidence of hyponatremia. Design: Descriptive research. Setting: The 2000 South African Ironman Triathlon, in which each athlete swam 3.8 km, cycled 180 km, and ran 42.2 km. Participants: All entrants in the race were invited to participate in the study. Methods: Athletes were weighed at registration, immediately prerace, immediately postrace, and 12 hours later. Blood samples were drawn at registration and immediately postrace. Rectal temperatures were measured postrace. Results: Starting body weight was significantly related to total finishing time (r = 0.27) and to cycling (r = 0.20) and running (r = 0.28) time. Body weight decreased significantly (p < 0.0001) during the race and had not returned to prerace values 12 hours later (p < 0.0001). Percentage change in body weight was unrelated to postrace rectal temperatures and inversely related to the postrace serum sodium concentrations (r = -0.45). Postrace serum sodium concentrations fell within a normal distribution (141.8 ± 3.1 mmol.L-1, mean ± SD) and were negatively correlated to overall triathlon time (r = -0.22). Three sodium values (0.6%) were below 135 mmol.L-1. Percentage change in body weight was unrelated to time in the marathon leg. Conclusions: Percentage change in body weight was linearly related to postrace serum sodium concentrations but unrelated to postrace rectal temperature or performance in the marathon. There was no evidence that in this study, more severe levels of weight loss or dehydration were related to either higher body temperatures or impaired performance.